Back Cover Image. Issue 1 (14th January 2020) - Liu, Yulun; Huang, Jing; Urbanowicz, Ryan J.; Chen, Kun; Manduchi, Elisabetta; Greene, Casey S.; Moore, Jason H.; Scheet, Paul; Chen, Yong
Abstract : Back Cover Caption: The cover image is based on the Original Article Embracing study heterogeneity for finding genetic interactions in large‐scale research consortia by Yong Chen et al., https://doi.org/10.1002/gepi.22262 .